PENGARUH PENAMBAHAN BEKATUL TERHADAP KADAR SERAT, AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK MINUMAN KEDELAI - Nurlitta Shafitri (2021)
Hypercholesterol is a condition where cholesterol levels in the blood exceed normal limits (>240 mg/dl). One of the alternative ways to prevent hypercholesterol is by decreasing high-fat food intake and increasing fiber and antioxidant intake. This study aims to analyze the effect of rice bran addition on fiber levels, antioxidant activity and organoleptic test of soybean drink and determine the selected formula and analyze the nutritional content of selected formulas. This research is an experimental study with a complete randomized design (CDR) one factor in the form of four treatments with the addition of rice bran by F0 (0%), F1 (6%), F2 (8%) and F3 (10%). Organoleptic test data was analyzed by using the Kruskal Wallis test and followed by using the Mann Whitney test if there were any significant differences. Food fiber test data and antioxidant activity were analyzed with the ANOVA test and continued with Duncan's test if there are significant differences. The results of organoleptic test analysis showed that the addition of rice bran had a significant effect (p<0.05) on the panelist's preferred level on the parameters of color, flavor, texture and taste of soybean drink. The results of analysis of dietary fiber and antioxidant activity showed that the addition of rice bran has a real effect (p<0.05) on food fiber levels and antioxidant activity of soybean drink. The formula selected in this study is F3 with the addition of 10% rice bran contains 10.23 grams food fiber content, 3094.18 ppm antioxidant activity, 1.80% protein content, 1.64% fat content, 6.49% carbohydrate content, 0.73% ash content and 89.34% ash content.